UTILIZATION Mangifera indica SKIN AND SALT AS ALTERNATIVE ENERGY - Ivan Maulana Akbar; Muna Mumtazah; Na’illah Ega Sivana; Adisty Virakawugi Darniwa; Ateng Supriyatna (Student Scientific Creativity Journal, 2023)
Efforts to reduce the use of polluting chemicals environment needs innovation to overcome these problems. One of them is by replacing the chemicals contained in the battery by utilizing mango skin waste became bio-battery. Even mango skin waste in the community is not properly utilized so that mango skin becomes waste that has no value. The purpose of this research is to utilize mango skin as a bio-battery material not only to produce current and voltage sources but it is also expected to be able to reduce the negative effects of disposing of community mango skin waste residue into the environment and reduce dependence on chemicals as battery electrolyte paste which has been used so far. The test parameters carried out were the electricity of the bio-baterry using mango skin and salt samples. This research used 3 weight ratios between mango skin solution and salt solution, namely 15:5 gr, 20 gr:5 gr, and 25:5 gr. The main stages of this research consisted of 3 stages, namely preparation, pH testing, characterization of electrical properties, and electrical analysis of mango skin. The results of the research that has been done, it can be concluded that the smallest measurements of pH, electric voltage, and electric current are produced at a volume of 30 ml (15 gr) of 3.55, 0.53 V, and 1.8 mA. While the highest was produced at a volume of 44 ml of 3.53, 1.53 V, and 1.9 mA.